2019
DOI: 10.1039/c8ee02751j
|View full text |Cite
|
Sign up to set email alerts
|

Lattice strain causes non-radiative losses in halide perovskites

Abstract: Halide perovskites are found to exhibit strain patterns over large areas, which influences the lifetimes of charge carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
442
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(461 citation statements)
references
References 50 publications
19
442
0
Order By: Relevance
“…J52:ITCCM‐O‐based device shows a high EQE EL of 2.4 × 10 –4 , corresponding to a quite small E loss,non‐rad of 0.22 eV, which is among the best result in reported OSCs . It should be noted that inorganic solar cells or perovskite solar cells usually have E loss,non‐rad of ~0.18 eV . As shown in Figure d, both the low driving force for charge generation and the low E loss,non‐rad contribute the low E loss and obtained high V OC .…”
Section: Resultsmentioning
confidence: 89%
“…J52:ITCCM‐O‐based device shows a high EQE EL of 2.4 × 10 –4 , corresponding to a quite small E loss,non‐rad of 0.22 eV, which is among the best result in reported OSCs . It should be noted that inorganic solar cells or perovskite solar cells usually have E loss,non‐rad of ~0.18 eV . As shown in Figure d, both the low driving force for charge generation and the low E loss,non‐rad contribute the low E loss and obtained high V OC .…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, Zhao et al first reported that the most perovskite films made by existing fabrication methods are strained due to the mismatched thermal expansion coefficients between perovskite films and substrates, and strain diminishes the long‐term stability of PSCs . Other studies confirmed the impact of strain on the stability of PSCs . The lattice strain in perovskite film has been proposed to impact ion migration, defect formation, and carrier dynamics in PSCs.…”
mentioning
confidence: 99%
“…Other studies confirmed the impact of strain on the stability of PSCs . The lattice strain in perovskite film has been proposed to impact ion migration, defect formation, and carrier dynamics in PSCs. Strain can be generated in perovskite films during device fabrication, thermal expansion, photostriction, electrostriction, or local lattice strain due to ionic size mismatch .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we performed similar temperaturedependent PL ( Figure S15, Supporting Information) and X-ray diffraction ( Figure S16, Supporting Information) measurements on mixed-cation (FA 0.80 MA 0.15 Cs 0.05 )Pb(I 0.83 Br 0.17 ) 3 samples (FA = formamidinium), which correspond to state-ofthe-art solar cell devices. [39,40] This work, focusing on low-temperature phase transitions, therefore provides unique insight into local strain properties, which ultimately lead to performance and stability issues at device operating temperatures. These observations are consistent with the FA-based samples exhibiting a more rigid lattice than their MA-counterparts, thereby inhibiting the phase transition and associated hysteresis effects in a similar manner to the constrained small grain samples.…”
mentioning
confidence: 99%